The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1177/0145721715606806
|View full text |Cite
|
Sign up to set email alerts
|

Family Model of Diabetes Education With a Pacific Islander Community

Abstract: Structured Abstract Purpose The purpose of this study is to use a community-based participatory approach to pilot test a family model of diabetes education conducted in participants’ homes with extended family members. Approximately 50% of Marshallese adults have type 2 diabetes, and prior attempts at diabetes education have not been shown effective due in large part to very high attrition. Research Design and Methods The pilot test included six families (27 participants) who took part in a family model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(86 citation statements)
references
References 29 publications
(23 reference statements)
1
72
0
Order By: Relevance
“…7–9,15 Prior studies evaluating DSME have failed to show glycemic control among participants. 16,17 Cultural adaption of DSME has been shown to be an effective strategy in other minority populations.…”
Section: Discussionmentioning
confidence: 99%
“…7–9,15 Prior studies evaluating DSME have failed to show glycemic control among participants. 16,17 Cultural adaption of DSME has been shown to be an effective strategy in other minority populations.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, McElfish, et al found that DSME in the home was effective when DSME was provided in a family setting in the home [11], but there is limited literature on this combined approach.…”
Section: Introductionmentioning
confidence: 99%
“…Stakeholders recommended that DSME be implemented within an extended family model so additional family members could benefit and the patient with diabetes would be supported by their family members (Hallgren et al, 2015; McElfish et al., 2016). Stakeholders continue to work side by side with researchers to culturally adapt DSME for implementation in a family model (McElfish, Bridges, et al, 2015). …”
Section: Process and Resultsmentioning
confidence: 99%